What Is Clinically Important in Lymphedema Management? A Systematic Review. Issue 1 (January 2018) - Tidhar, Dorit; Armer, Jane M.; Stewart, Bob R.
Abstract : Objective: To summarize published reports on the clinical effectiveness of conservative lymphedema management by reporting on outcomes that use anchor- and distribution-based approaches. Data Sources: MEDLINE and EBSCO databases from inception to April 2017. Study Selection: Articles were selected if they included an estimate for minimal clinically important difference (MCID). Data Synthesis: Twenty-four articles involving 938 patients met our inclusion criteria. Years of publication ranged from 1991 to 2016. Of these, 16 studies examined outcomes after the intervention was completed. The other 8 studies tested the reliability of measurement tools. Data were stratified according to different outcomes: limb volume (20 studies, 785 patients), symptoms (6 studies, 288 patients), skin changes (1 study, 28 patients), infection rate (5 studies, 255 patients), quality of life (4 studies, 148 patients), and strength, function, endurance, fitness, and disability (3 studies, 89 patients). Most studies covered cancer-related lymphedema (22/23), especially as related to breast cancer (19/22). Large heterogeneity was found in the methods of estimations with regard to improvement, exacerbation, and stability of lymphedema. Conclusion: There is limited evidence to draw conclusions regarding the recommended MCIDs for different populations, outcomes, and periods of time. Further studies are needed to facilitate the process of improving clinical care of lymphedema.